Ontology of Early Childhood Education in Fairy Tale Books Published by Naura: a Case Study at RA Rumah Kreatif Wadas Kelir - Prawening, Cesilia; Musyafa Ali; Seftia Wijayanti (JOYCED: Journal of Early Childhood Education, 2025)
This study aims to evaluate the alignment of fairy tale books published by Naura with moral values and reasoning that are appropriate for early childhood.and its relevance to child development at RA Rumah Kreatif Wadas Kelir. Ontology in this context is interpreted as a fundamental study of the nature of values, character, and the formation of children's personalities which are represented through the storyline, characters, and moral messages in fairy tales.This study also examines whether these stories meet the criteria for quality literature that supports moral development in accordance with the developmental characteristics of early childhood. This study uses a qualitative descriptive method with a content analysis approach, combined with a case study design at RA Rumah Kreatif Wadas Kelir. The research findings indicate that Naura's fairy tale books effectively convey moral values relevant to children's daily experiences, such as obedience and perseverance. These values align with the typical moral reasoning stage in early childhood, which, according to Kohlberg's theory, corresponds to the pre-conventional level. The narratives presented in these books have ontological implications for early childhood education, particularly in fostering and supporting the moral development of young learners.The stories in this book can be a fun character learning medium, making it easier for teachers to instill good values, and supporting the formation of children's self-identity based on story literacy, while also providing practical recommendations for educators in optimizing the use of story books as a character learning medium.